Indirect co‐cultures of healthy mesenchymal stem cells restore the physiological phenotypical profile of psoriatic mesenchymal stem cells - Campanati, A. (Clin Exp Immunol, 2018)
Psoriasis microenvironment, characterized by an imbalance between T helper type 1 (Th1)/Th17 and Th2 cytokines and also influences the mesenchymal stem cells (MSCs) phenotypical profile. MSCs from healthy donors (H‐MSCs) can exert a strong paracrine effect by secreting active soluble factors, able to modulate the inflammation in the microenvironment. To evaluate the influence of H‐MSCs on MSCs from psoriatic patients (PsO‐MSCs), H‐MSCs and PsO‐MSCs were isolated and characterized. Indirect co‐culture of H‐MSCs with PsO‐MSCs was performed; effects on proliferation and expression of cytokines linked to Th1/Th17 and Th2 pathways were assayed before and after co‐culture. The results show that before co‐culture, proliferation of PsO‐MSCs was significantly higher than H‐MSCs (P < 0·05) and the levels of secreted cytokines confirmed the imbalance of Th1/Th17 versus the Th2 axis. After co‐culture of H‐MSCs with PsO‐MSCs, healthy MSCs seem to exert a ‘positive’ influence on PsO‐MSCs, driving the inflammatory phenotypical profile of PsO‐MSCs towards a physiological pattern. The proliferation rate decreased towards values nearer to those observed in H‐MSCs and the secretion of the cytokines that mostly identified the inflammatory microenvironment that characterized psoriasis, such as interleukin (IL)‐6, IL‐12, IL‐13, IL‐17A, tumour necrosis factor (TNF)‐α and granulocyte–macrophage colony‐stimulating factor (G‐CSF), is significantly lower in co‐cultured PsO‐MSCs than in individually cultured PSO‐MSCs (P at least < 0·05). In conclusion, our preliminary results seem to provide an intriguing molecular explanation for the ever‐increasing evidence of therapeutic efficacy of allogeneic MSCs infusion in psoriatic patients.